Analisis Penambahan Limbah Kardus Terhadap Kuat Tekan dan Tarik Belah Pada Beton Normal - Belva Prana Firzatulloh; Ganjar Jojon Johari; Adhitya Surya Pratama (Jurnal Konstruksi, 2025)
Concrete is a widely used material and is the main element in buildings. Along with the increase in infrastructure development, the use of cardboard is also increasing in the industrial or community sector. However, with the increase in the use of cardboard, cardboard waste increases. This study examines the use of cardboard pulp as an additive. Cardboard pulp has oxide compounds such as silica. The purpose of this study was to determine the comparison of the compressive and tensile split strength values of concrete for 28 days by adding cardboard waste with a mixture variation of 0%, 5%, 10%, and 15% by weight of fine aggregate. The research was conducted using experimental methods in the laboratory. Concrete mix planning in this study refers to SNI 7656, 2012, testing the compressive and split tensile strength of concrete using a CTM (Compression Testing Machine) tool. Based on the results of testing the compressive strength and split tensile strength of concrete after 28 days of age, the highest average value of compressive strength of concrete with a mixture of 5% variation cardboard pulp worth 15.76 MPa and the lowest is concrete with a mixture of 15% variation cardboard pulp worth 6.12 MPa. and the highest average value of split tensile strength is concrete with a mixture of 10% variation cardboard pulp worth 1.22 MPa and the lowest is concrete with a mixture of 15% variation cardboard pulp worth 0.85 MPa.